2022
DOI: 10.3390/metabo12070581
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Metabolomics Study of the Impact of Articaine and Lidocaine on the Metabolism of SH-SY5Y Neuronal Cells

Abstract: Articaine (ATC) and lidocaine (LDC) are the local anesthetics (LAs) currently most employed in dentistry. Cases of paresthesia, reported more frequently for ATC, have raised concerns about their potential neurotoxicity, calling for further investigation of their biological effects in neuronal cells. In this work, the impact of ATC and LDC on the metabolism of SH-SY5Y cells was investigated through 1H NMR metabolomics. For each LA, in vitro cultured cells were exposed to concentrations causing 10 and 50% reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Mitochondria are commonly referred to as energy factories, responsible for the conversion of nutrients such as glucose, lipids, and amino acids into ATP through the electron transport chain and oxidative phosphorylation . Glucose can be decomposed into pyruvate, which is in turn decarboxylated to acetyl CoA and enters the tricarboxylic acid cycle . Fatty acids, undergoing β oxidation, could also ultimately cleave into acetyl CoA and enter the tricarboxylic acid cycle .…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondria are commonly referred to as energy factories, responsible for the conversion of nutrients such as glucose, lipids, and amino acids into ATP through the electron transport chain and oxidative phosphorylation . Glucose can be decomposed into pyruvate, which is in turn decarboxylated to acetyl CoA and enters the tricarboxylic acid cycle . Fatty acids, undergoing β oxidation, could also ultimately cleave into acetyl CoA and enter the tricarboxylic acid cycle .…”
Section: Results and Discussionmentioning
confidence: 99%
“…61 Glucose can be decomposed into pyruvate, which is in turn decarboxylated to acetyl CoA and enters the tricarboxylic acid cycle. 62 Fatty acids, undergoing β oxidation, could also ultimately cleave into acetyl CoA and enter the tricarboxylic acid cycle. 63 Hence, the alleviated glycolipid disorders could be, at least partially, related with recovered impairment of RCC I (a membranebound component of the tricarboxylic acid cycle 64 ), RCC IV (a rate-limiting enzyme for ATP synthesis 65 ), and RCC V (another key enzyme for ATP production).…”
Section: Nr Supplementation Suppressed Dbdpe-induced Mitochondrial Dy...mentioning
confidence: 99%
“…Our analysis also showed that conformational restriction was crucial for improving the binding on Na V 1.7 and Na V 1.8, but not of Na V 1.5. In addition, we explored the modifications of the methyl ester, which is known to undergo rapid hydrolysis 35 . Remarkably, as the steric hindrance increased up to n- propyl ( AT-28 ), binding to Na V 1.7 improved before decreasing again.…”
Section: Resultsmentioning
confidence: 99%
“…NMR metabolomics allows to identify the entire metabolite spectrum in many biological fluids and cellular extract/medium, obtaining a metabolic fingerprint (metabolic profile) that characterizes the healthy or diseased state [7]. NMR spectroscopy, compared to other techniques, has the advantage of being rapid and not requiring a particular treatment of the samples [8].…”
Section: Of 12mentioning
confidence: 99%